Long-term effects of anti-N-methyl-d-aspartate receptor encephalitis on quality of life - Hirose, Satoshi; Hara, Makoto; Yokota, Yuki; Nakajima, Hideto (Frontiers in Neurology, 2023)
Background Patients with anti-N-methyl-d-aspartate receptor encephalitis (NMDARE) usually achieve neurologically favorable outcomes in the post-acute-phase. Even when motor function recovers, many patients experience numerous non-motor sequelae and cannot resume their pre-NMDARE lives even years later. Additionally, the needs of patients with NMDARE may impose a severe caregiver burden. Unfortunately, few studies have comprehensively examined patients recovering from NMDARE. We investigated the long-term effects of NMDARE on patients’ quality of life (QOL). Methods Data collected via structured self-reported questionnaires included clinical features, long-term outcomes, and QOL. These questionnaires were administered to adult members of the Japanese Anti-NMDARE Patients’ Association. We used the NeuroQOL battery to assess QOL in physical, mental, and social domains. Raw NeuroQOL scores were converted to T-scores for comparison with controls. Results Twenty-two patients completed the questionnaire. The median interval between disease onset and questionnaire response was 78 months. Forty-six percent of patients reported persistent sequelae, with only 73% able to resume prior work/school activities. Although patients’ Global QOL was similar to controls, patients with NMDARE had significantly worse social QOL. Patients with worse social QOL had more frequent sequelae than those with better social QOL. Furthermore, patients with persistent sequelae had significantly worse Global QOL than those without sequelae and controls. Conclusion Patients with NMDARE had worse social QOL than controls. Given the adverse effects of disease sequelae on QOL, treatment strategies that minimize sequelae during the acute-phase may improve patients’ QOL, even years post-disease onset.